Common and rare alleles of the serotonin transporter gene, SLC6A4, associated with Tourette's disorder. Issue 9 (29th April 2013) - Moya, Pablo R.; Wendland, Jens R.; Rubenstein, Liza M.; Timpano, Kiara R.; Heiman, Gary A.; Tischfield, Jay A.; King, Robert A.; Andrews, Anne M.; Ramamoorthy, Samanda; McMahon, Francis J.; Murphy, Dennis L.
ABSTRACT To evaluate the hypothesis that functionally over‐expressing alleles of the serotonin transporter (SERT) gene (solute carrier family 6, member 4, SLC6A4) are present in Tourette's disorder (TD), just as we previously observed in obsessive compulsive disorder (OCD), we evaluated TD probands (N = 151) and controls (N = 858). We genotyped the refined SERT‐linked polymorphic region 5‐HTTLPR/rs25531 and the associated rs25532 variant in the SLC6A4 promoter plus the rare coding variant SERT isoleucine‐to‐valine at position 425 (I425V). The higher expressing 5‐HTTLPR/rs25531 LA allele was more prevalent in TD probands than in controls (χ2 = 5.75; P = 0.017; odds ratio [OR], 1.35); and, in a secondary analysis, surprisingly, it was significantly more frequent in probands who had TD alone than in those who had TD plus OCD (Fisher's exact test; P = 0.0006; OR, 2.29). Likewise, the higher expressing LAC haplotype (5‐HTTLPR/rs25531/rs25532) was more frequent in TD probands than in controls (P = 0.024; OR, 1.33) and also in the TD alone group versus the TD plus OCD group (P = 0.0013; OR, 2.14). Furthermore, the rare gain‐of‐function SERT I425V variant was observed in 3 male siblings with TD and/or OCD and in their father. Thus, the cumulative count of SERT I425V becomes 1.57% in OCD/TD spectrum conditions versus 0.15% in controls, with a recalculated, family‐adjusted significance of χ2 = 15.03 (P < 0.0001; OR, 9.0; total worldwide genotyped, 2914). This report provides a unique combination of common and rare variants in one gene in TD, all of which are associated with SERT gain of function. Thus, altered SERT activity represents a potential contributor to serotonergic abnormalities in TD. The present results call for replication in a similarly intensively evaluated sample. © 2013 Movement Disorder Society